Design and fabrication of natural woven fabric reinforced epoxy composite for household telephone stand - Sapuan, S. M.; Maleque, Md. Abdul (Elsevier, 2005)
In the recent era there has been an increasing interest in composite materials for its applications in the field of aerospace, sports, industries, medical, and in many other fields of engineering including household furniture. This paper deals with the design and fabrication of banana woven fabric reinforcement epoxy composite for household telephone stand. A systematic approach of total design process is presented for better understanding of the best design concept for the product. The fabrication process of composite telephone stand using banana woven fabric is also described in this paper.